Nutrition practices with a focus on parenteral nutrition in the context of enhanced recovery programs: An exploratory survey of gastrointestinal surgeons. (August 2022) - Durán-Poveda, Manuel; Bonavina, Luigi; Reith, Bernd; Caruso, Rosario; Klek, Stanislaw; Senkal, Metin
Summary: Background & aims: Ensuring patients have adequate physiological reserves to meet the demands of major surgery may necessitate nutritional prehabilitation and perioperative medical nutrition therapy (MNT). Parenteral nutrition (PN) via central or peripheral routes is indicated when requirements cannot be met orally or enterally. While patients undergoing major gastrointestinal (GI) surgery are at high nutritional and catabolic risk, guidance on PN is limited in Enhanced Recovery After Surgery (ERAS) protocols. This survey-based study characterized MNT practices among GI surgeons, and the challenges and opportunities for MNT within the context of ERAS. Methods: This on-line survey comprised questions and attitudinal statements centred on MNT, particularly PN, for major GI surgery patients, and encompassed the spectrum of the surgical pathway (prehabilitation to postoperative care). GI surgeons in Europe were invited to complete the survey. Respondents described their current clinical practices, while their perceptions, unmet needs, and opportunities to improve nutritional management were explored via Likert-scale responses to statements. Results: GI surgeons (N = 130) from different centres in France, Germany, Italy, Poland, and Spain completed the survey. Enhanced recovery protocols (75%) and multidisciplinary nutritional care teams (72%) were established in the centres of most respondents; surgeons, dieticians/nutritionists, and nurses were most frequently involved in MNT. Nutritional risk screening was common in the centres surveyed prior to surgery (range: 62% in Italy to 96% in Poland) and undertaken less frequently postoperatively (range: 19% in Poland to 54% in Germany) with varied screening methods. Enteral nutrition insufficiency was the most common reason for prescribing PN (83%) and 56% of surgeons prescribed PN when enteral nutrition (EN) was not feasible. Overall, 71% of respondents agreed that peripherally administered PN (PPN), which does not require a central access route, lessens invasive procedures and benefits selected patients who are in a catabolic state, malnourished, or at nutritional/metabolic risk when oral intake/EN is insufficient. However, only 35% of surgeons used PPN in this scenario and only 47% utilized PPN when a central venous catheter is not available. Most surgeons (69%) agreed that PPN is in line with the ERAS concept of using minimally invasive approaches. The respondents raised a need for increasing awareness of PPN indications (81%), inclusion of PPN recommendations in clinical guidelines (79%), implementation of nutritional support teams (79%), and increased PPN-trained personnel (78%) to improve PPN delivery. Conclusions: PPN is perceived by surgeons (with ≥10 patients per month who receive PN) as a favourable strategy to support timely nutritional support in selected patients undergoing major GI surgery. However, from this clinical practice survey it seems PPN is underutilized in nutritional care practices. Findings from this survey of GI surgeons in Europe emphasize the need to improve early identification of patients who are malnourished or at nutritional/metabolic risk and integrate PPN into ERAS GI surgical pathways, within the framework of minimally invasive approaches. Graphical abstract: Image 1 Highlights: PPN facilitates timely nutrition when oral/enteral support is inadequate. PPN supports the ERAS concept of using minimally invasive approaches. PPN may improve prehabilitation and perioperative care of major GI surgery patients. Many GI surgery patients who would benefit from PPN do not receive this therapy. Earlier identification of GI surgical patients at nutritional risk is needed.